Information technology and quality management to strengthen the civic education of citizens - Velarde Guevara, Jannet Yajaira (2018)
This article develops a topic of interest to scholars and researchers as is that of the new technologies of information and communication as well as the quality management. The central theme is the use made by the public institutions of the technologies of information and communication technologies, and how these govern its development through quality processes. The methodology includes all operational aspects that are taken into account for the study. In this scientific research has been dominated by three basic methods: Induction, analysis and synthesis. The main conclusions presented here demonstrate the importance it has today the use of information and communication technologies and how they can help processes and procedures in place in different organizations; quality management is necessary because it allows you to measure the effectiveness and impact of information technologies on population of the district of Ate in metropolitan Lima, and how you can replicate in different parts of the country. This article is the product of the work of the author, that maestrista on the use that give public institutions to technologies of information and communication, as well as the quality management which must be implicit in its processes.